THE IMPACT OF SOCIAL FACTORS OF MONGOLIA’S DEFENSE POLICY ON NATIONAL RESILIENCE - Nergui Bayartogtokh; Delgermaa Paashaa; Uranchimeg Tumurbat (International Journal of Innovative Technologies in Social Science, 2025)
In today’s world, the security environment is becoming increasingly complex and multifaceted, with rapidly evolving threats impacting the stability of both domestic and international affairs. The nature and methods of these threats are constantly changing, challenging both traditional and emerging security concepts. This has created an urgent need for nations to develop adaptive capacities to effectively respond to and withstand such risks. In this context, strengthening national resilience to external negative influences while fostering internal unity has become a crucial strategic priority for many countries. For Mongolia, enhancing national resilience against modern multidimensional threats and refining its defense policy to incorporate social factors is a key strategic instrument for ensuring national security. This paper provides a scientific analysis of the contemporary security environment, the nature of hybrid warfare threats, the characteristics of national resilience, and the role and influence of defense policy, particularly its social dimensions. Furthermore, it outlines necessary measures to enhance national resilience against emerging security challenges.